Comparison of craniotomy surgery therapy with conservative medical therapy in haemorrhagic stroke patients RSUD Dr Chasbulah Abdul Majid Bekasi City January-December 2022 - Utomo, Tranggono Yudo (International Journal Labs, 2024)
Hemorrhagic stroke is caused by rupture of blood vessels in the brain, which causes blood to leak into the brain tissue. As a result, the oxygen supply to brain cells is disrupted because blood cannot flow through the ruptured blood vessels. There are two main options for treating hemorrhagic stroke, namely surgical therapy and conservative therapy. The aim of this study was to compare the results of surgical therapy and conservative therapy in hemorrhagic stroke patients at RSUD Dr. Chasbulah Abdul Majid Bekasi City during the period January to December 2022. The type of research used by researchers is retrospective descriptive research. Data were collected from medical records of patients who had undergone surgical therapy and conservative therapy for hemorrhagic stroke. The statistical analysis used is descriptive statistics using frequency analysis. Research findings showed that more patients showed improved prognosis after using conservative therapy, with a percentage reaching 85.5%. Meanwhile, for patients who underwent operative therapy, the percentage of improvement in prognosis was 65.4%. It can be concluded that the percentage of improvement in patient prognosis after receiving conservative therapy is higher than those receiving operative therapy.